2020
DOI: 10.1002/ijc.33199
|View full text |Cite
|
Sign up to set email alerts
|

Germline pathogenic variant spectrum in 25 cancer susceptibility genes in Turkish breast and colorectal cancer patients and elderly controls

Abstract: Inherited pathogenic variants account for 5% to 10% of all breast cancer (BC) and colorectal cancer (CRC) cases. Here, we sought to profile the pathogenic variants in 25 cancer susceptibility genes in Turkish population. Germline pathogenic variants were screened in 732 BC patients, 189 CRC patients and 490 cancer-free elderly controls, using next-generation sequencing-based multigene panel testing and multiplex ligation-dependent probe amplification testing. Pathogenic variants were detected in 17.2% of high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…The rate of pathogenic variants (PVs) identified with multigene NGS panel testing in Turkish patients with BC was 15.8% in our study. Most of these PVs were BRCA1 and BRCA2 genes (~39%), which is consistent with previous literature ( 16 , 19 ). Furthermore, the prevalence of BRCA1/2 mutations in the CG was 6.7% and in those with FH of BC was 14.1%, which was similar to the literature in which the prevalence ranges from 9 to 21% ( 20 22 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The rate of pathogenic variants (PVs) identified with multigene NGS panel testing in Turkish patients with BC was 15.8% in our study. Most of these PVs were BRCA1 and BRCA2 genes (~39%), which is consistent with previous literature ( 16 , 19 ). Furthermore, the prevalence of BRCA1/2 mutations in the CG was 6.7% and in those with FH of BC was 14.1%, which was similar to the literature in which the prevalence ranges from 9 to 21% ( 20 22 ).…”
Section: Discussionsupporting
confidence: 92%
“…In Turkey, Large Genomic Rearrangements (LGRs). rates are between 1-4% (19,24,25) comparable with different populations around the world (0.1-12.7%) (16,(26)(27)(28)(29)(30).…”
Section: Positive In Gene Categoriesmentioning
confidence: 68%
See 2 more Smart Citations
“…As summarized in Table 1 , among 22 FANC genes, FANCS/BRCA1 and FANCD2/BRCA2 , high-risk hereditary breast-ovarian cancer syndrome susceptibility genes, are the most investigated as CRC susceptibility genes beyond its well-known predispositions [ 27 , 28 , 29 , 30 , 31 , 44 , 73 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Recent findings revealed that the prevalence of BRCA1/2 PVs among early-onset (1.3%) [ 30 ] and unselected patients with CRC (3.9%) [ 88 ] is more frequent than would be happening by chance.…”
Section: Potential Role Of Fanc Gene Mutations In ...mentioning
confidence: 99%